Development of soft and hard skills with a better employability vision for engineering students - Martínez-Gómez, Javier; Nicolalde, Juan Francisco (Frontiers in Education, 2025)
This study explores how participation in research projects can enhance both soft and technical skills among engineering students, contributing to greater employability. Students developed key competencies such as teamwork, leadership, responsibility, and technical proficiency by integrating problem-based learning methodologies into research initiatives. Survey results indicated high levels of self-reported improvement in these skills and increased academic motivation. The findings suggest that involving students in structured research projects offers a valuable pathway to address employability gaps in engineering education.